Segmentación laboral en Colombia durante el período 2001-2006 (2011)
A job is a guarantee of income and, at the same time, a space of development. However, dealing with labor precariousness, today it is important for an individual to find employment, but a good one. The problem of entry to the best occupations would be less important if people could do it just improving their labor productivity; other complications appear when there are barriers of entry other than human capital, as the labor market segmentation theory says. In this context, this document has the objective of showing the existence of a segmented labor market in Colombia during the period 2001-2006. Through several econometric models, it is proved that using the scale of firms for dividing the labor market in two parts leads to find a primary and a secondary segment, being the first the one which groups the best occupations and has a restricted access